Discovery of New Thioviridamide‐Like Compounds with Antitumor Activities. Issue 10 (26th August 2019) - Li, Yuqing; Liu, Jingyu; Tang, Haoyu; Qiu, Yanping; Chen, Dandan; Liu, Wen
Summary of main observation and conclusion: Thioviridamide is a structurally unique compound with potent antitumor activity. The biosynthesis of thioviridamide follows a typical pathway as ribosomally synthesized and post‐translationally modified peptides, making the genome mining‐based discovery of thioviridamide‐like compounds rational. Taking advantage of the linkage between the precursor peptide and the metabolite skeleton, we identified a new biosynthetic gene cluster in Streptomyce s sp. NRRL S‐87 that could encode thioviridamide analogues. Overexpression of the whole gene cluster led to the isolation and structure elucidation of TVA‐YJ‐4 and TVA‐YJ‐5, two novel thioviridamide‐like compounds featuring N ‐terminal capping groups. Chemical screening of the fermentation extracts also detected TVA‐YJ‐6, another new thioviridamide‐like compound with representative methionine sulfoxide. Detailed analysis further revealed that these structural modifications were introduced during the compound extraction process instead of through genuine enzymatic reactions. TVA‐YJ‐4 and TVA‐YJ‐5 display slightly reduced cytotoxic activities against a panel of tumor cell lines in comparison with their parental natural product, TVA‐YJ‐2. Our work will expand the membership of this rare class of compounds and promote related biosynthetic studies. Abstract : Discovery of novel antitumor thioviridamide‐like compounds provides an insight into the structural modifications during the compound extraction process.